Term Structure Modelling by Using Nelson-Siegel Model - Hana Hladíková; Jarmila Radová (European Financial and Accounting Journal, 2012)
Zero coupon rates are not observable in the market for a range of maturities. Therefore, an estimation methodology is required to derive the zero coupon yield curves from observable data. If we deal with approximations of empirical data to create yield curves it is necessary to choose suitable mathematical functions. We use parametric model of Nelson and Siegel. The current mathematical apparatus employed for this kind of approximation is outlined. This theoretical background is applied to an estimation of the zero-coupon yield curve derived from the Czech coupon bond market. There are many methodologies and each can provide surprisingly different results. Nevertheless, each seeks to provide an estimation that fit the data well while maintaining an easily interpretable form. On an initial test data sample we have not faced any problems, reported elsewhere, of not having found the global optimum or having found multiple local minima.
Keywords: G30; G60; M30; 650; Yield curve estimation; Nonlinear least squares; Nelson-Siegel model